Table 1_Gut microbiota alterations and systemic inflammation in community-acquired pneumonia: a prospective gut-lung axis study.docx - Xue-Qin Yang (3494345) (2025)
Up to now, only a few scattered studies have provided some evidence for the relationship between gut microbiota and community-acquired pneumonia (CAP), and the mechanisms by which gut microbiota contributes to the occurrence and development of CAP via the gut-lung axis require further investigation. In this study, fecal and serum samples from CAP patients and healthy controls were analyzed using 16S rRNA gene sequencing and enzyme-linked immunosorbent assay. The results showed that compared with healthy controls, alpha-diversity of gut microbiota in CAP patients was significantly reduced, and beta-diversity was significantly different at operational taxonomic units (OTUs), class, order, family, genus, and species levels. The abundance of short-chain fatty acid-producing genera in CAP patients decreased significantly, such as Blautia and Agathobacter. Meanwhile genera including Gemmiger, Enterocloster, and Thomasclavelia were enriched in the CAP. Functional predictions based on KEGG Orthologies suggested that the gut microbiota of CAP patients was enriched in pathways related to carbohydrate metabolism and bacterial infection. Serum detection revealed that the levels of lipopolysaccharide (LPS), TNF-α, and IL-6 were significantly increased in CAP patients. Our findings suggest that gut microbiota dysbiosis in CAP patients is associated with increased translocation of LPS into the bloodstream and activation of systemic inflammation, indicating that the gut-lung axis may play a potential role in the pathogenesis of CAP.